Low level laser therapy in management of post endodontic retreatment pain: A review - V. K. Humnabad; R. Kashikar; A. Hindlekar; S. R. Srinidhi; S. Sh. Adapa (Эндодонтия Today)
Post-endodontic treatment pain is frequent which needs analgesics for patient’s pain relief. One of the most common reasons for post operative pain is chemical, mechanical, or microbial injuries to the periapical tissues that result in acute inflammation. Application of recently developed endodontic techniques and devices will reduce postoperative pain. Two proven methods for reducing pain associated with inflammation are low-level laser therapy (LLLT) and antimicrobial photodynamic therapy. The use of LLLT in root canal therapy procedures is supported by more and better-documented evidence.